Inspection of viscoelastic Ag+Cu+Fe3O4+Al2O3/kerosene oil tetra-hybrid nanofluid flow across a stretchable rotating disk with exponentially varying viscosity - Bhagyashri Patgiri; Ashish Paul (Journal of Taibah University for Science, 2024)
Fluid flow through rotating disks plays a critical role in various applications across daily life, engineering, and industry, including rotor-stator systems, ocean circulation models, and medical equipment. This study investigates the potential of a novel fluid type – tetra-hybrid nanofluids – in such applications. We explore the influence of factors like variable viscosity, thermal radiation, suction/injection, thermophoresis, nanoparticle shape, Deborah number, and Brownian motion on the flow characteristics of a viscoelastic tetra-hybrid nanofluid over a stretchable rotating disk. Employing the bvp4c numerical scheme, we analyze the governing dimensionless equations. The results demonstrate that the tetra-hybrid nanofluid exhibits significantly improved heat transfer rates compared to conventional nanofluids, hybrid nanofluids and tri-hybrid nanofluids with enhancements of 7.43%, 6.27%, and 5.35%, respectively. Additionally, the study reveals that lamina-shaped nanoparticles offer higher heat transport performance compared to spherical and blade-shaped nanoparticles.